The impact of the COVID-19 pandemic on the quality of life of post-stroke patients in the southern region of Kazakhstan - M.I. Assylbek; M. Anartaуeva; N. Zharkynbekova; G. Sarsenbayeva; K. Kemelbekov (Central Asian Journal of Medical Hypotheses and Ethics)
The study subjects were patients from the Turkestan region who had experienced a stroke. The specificity of the sampling approach was to cover the widest possible range of individuals to ensure the representativeness of the results. The inclusion of patients from different age groups, genders, socio-economic statuses, and ethnic backgrounds allowed to obtain reliable results on the impact of the pandemic on the quality of life after a stroke in this region. Given that strokes differ in severity and consequences, the sample included patients with different forms and stages of post-stroke rehabilitation. The inclusion of such patients allowed to assess both the short-term and long-term impact of the pandemic on the quality of life in various subgroups of stroke survivors. The focus on the Turkestan region allowed to analyze the regional aspects of healthcare and social structure, as well as their impact on the availability of medical services and overall support for patients during the pandemic. The purpose of the study was to investigate the impact of the COVID-19 pandemic on the quality of life of patients who have had a stroke.